Safety climate in English general practices: workload pressures may compromise safety. Issue 1 (16th August 2015) - Bell, Brian G.; Reeves, David; Marsden, Kate; Avery, Anthony
Abstract: Objectives: Although most health care interactions in the developed world occur in general practice, most of the literature on patient safety has focused on secondary care services. To address this issue, we have constructed a patient safety toolkit for English general practices. We report how practice and respondent characteristics affect scores on our safety climate measure, the PC‐Safequest, and address recent concerns with high levels of workload in English general practices. Methods: We administered the PC‐Safequest, a 30‐item tool that was designed to measure safety climate in primary care practices, to 335 primary care staff members in 31 practices in England. Practice characteristics, such as list size and deprivation in the area the practice served, and respondent characteristics, such as whether the respondent was a manager, were also collected and used in a multilevel analysis to predict PC‐Safequest scores. Results: Managers gave their practices significantly higher safety climate scores than did non‐managers. Respondents with more years of experience had a more negative perception of the level of workload in their practice. Practices with more registered patients and in areas of higher deprivation provided lower safety climate scores. Conclusions: Managers rated their practices more positively on our safety climate measure, so the differences between the perceptions of managers and other staff may need to be reduced in order to build a strong safety culture. Excessive workload for more experienced staff and lower safety climate scores for larger practices may reflect 'burnout'. Concerns that pressures in primary care could affect patient safety are discussed.